Recruitment and Job Search Application - Khaleel, Firas Layth (2011)
Web based online applications become the most useful tools to access the information about job applicants and job applications are accessible at the press of a button. The progress of Internet and World Wide Web technology brings the traditional recruitment process to web based recruitment. A recruitment and job search application system allow candidates to search for jobs anywhere anytime, helping people to find suitable work relevant to their needs. This study focused on how to recruit the job seeker through the internet, where it is expensive for job seekers to find jobs in the traditional way. It is also the problem for the employers to find suitable candidates regardless of gender, location, or nationality. The main purpose of this project is to enable employers to search for suitable candidates according to the requirements of organization, as well as allowing job seekers to search and select the availability of jobs suitable for their needs. This problem is solved by using and applying the general methodology. Two types of criteria are selected and designed to improve the quality of result for job seeker and employer. The project use Java script and Database MYSQL, is tested using (Black Box Test (Functional testing)) for all functionality.